SUATU PANDANGAN TEOLOGI LUTHERAN TENTANG LITURGI IBADAH SEBAGAI KESAKSIAN IMAN GEREJA - Natanael, Mikhael (Sekolah Tinggi Teologi Adhi Wacana Surabaya, 2025)
In the modern era, many churches have developed worship systems that tend towards pragmatism, often at the expense of liturgical depth. While the diversity of liturgical forms should rightly be regarded as a strength within the Protestant tradition, attention must nonetheless be paid to how the Reformers preserved their theological convictions, particularly in relation to worship. Lutheran theology, in particular, exhibits a broadly conservative stance on liturgy, and its historical‑grammatical interpretation of biblical texts concerning worship remains pivotal in shaping a robust liturgical paradigm. Furthermore, the confessional heritage of the church has been meticulously conserved well into the contemporary period. Yet, scholarly engagement with the underlying theological framework of liturgy in ecclesial practice remains relatively scarce. This study therefore presents a theological perspective drawn from the Lutheran tradition on the nature and purpose of corporate worship. Employing a comprehensive literature review, it investigates both the biblical texts and the confessional documents of the church, demonstrating that liturgy is not merely a ceremonial sequence but a typology of the Christian life that is both missional and communal.